2013
DOI: 10.1002/adma.201303124
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanodots Featuring Efficient FRET for Real‐Time Monitoring of Drug Delivery and Two‐Photon Imaging

Abstract: A FRET-based carbon nanodot (CDot) drug delivery platform has been developed. These CDots offer excellent biocompatibility, stable fluorescence, and efficient FRET between CDots and the attached fluorescent drug molecules, such as doxorubicin, enabling enhanced drug delivery, convenient cell imaging, and real-time monitoring of drug release. Moreover, the FRET-based two-photon imaging and drug tracking in deep tissues are also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
353
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(359 citation statements)
references
References 43 publications
4
353
0
2
Order By: Relevance
“…Previously, other novel methods have been suggested to monitor drug release such as Fӧrster resonance energy transfer (FRET). However, FRET is used mainly to measure release of fluorescent drug molecules, 31 whereas DPV can be used for both fluorescent and nonfluorescent molecules. The drug release profiles obtained by the DPV method corroborates the results of the UV-Vis detection method.…”
mentioning
confidence: 99%
“…Previously, other novel methods have been suggested to monitor drug release such as Fӧrster resonance energy transfer (FRET). However, FRET is used mainly to measure release of fluorescent drug molecules, 31 whereas DPV can be used for both fluorescent and nonfluorescent molecules. The drug release profiles obtained by the DPV method corroborates the results of the UV-Vis detection method.…”
mentioning
confidence: 99%
“…212 According to the experimental results and theoretical simulations, they found that graphitic-C 3 N 4 QDs emit strong blue fluorescence at 400 nm and green emission under one-photon UV excitation and two-photon excitation at 780 nm. In addition to these successful syntheses of carbon-based QDs, the conduction of TPF microscopy made water-dispersed and biocompatible carbon QDs, which might offer new advantages in biosensing, drug delivery, two-photon photodynamic cancer therapy, 213 cellular tracking 212,214,215 and deep-tissue imaging. 209 Ray et al also reported that graphene oxide featured an extremely high 46 890 GM of TPA for selective two-photon imaging of SK-BR-3 breast tumor cells.…”
Section: Nir-absorbing Organic Materials: Dyes and Polymersmentioning
confidence: 99%
“…For example, Zheng and colleagues designed DOX-conjugated C-dots to perform drug delivery in HeLa cells. 214 Two-photon excitation of 810 nm femtosecond sources on C-dots exhibited emission coupling with the excitation band of DOX, thereby evolving an efficient FRET and generating strong red fluorescence at pH 7.4 for glomerular tissues (z-direction at a depth of 65 − 300 μm), whereas the red color emission was depleted when the particles were delivered to the cell body (pHo5). Intriguingly, Chen and co-workers employed a two-photon excitation FRET strategy to excite a 5,10,15,20-tetrakis(1-methyl 4-pyridinio) porphyrin PS, which caused HeLa cell death through PDT.…”
Section: Nir-absorbing Organic Materials: Dyes and Polymersmentioning
confidence: 99%
“…They are produced by size reduction from various carbon sources. 27,28 Their fluorescence spectrum is usually dependent on excitation wavelength with a relatively low quantum yield of lower than 15%. [29][30][31] The carbon dots formed through bottom-up approaches are more well known because of their facile synthesis and outstanding fluorescence quantum yield.…”
mentioning
confidence: 99%